# Slanting triangles

Even for triangles shaped as below, the area of a triangle = base x height and half it.

The proof (but you don’t need it) is as follows:

Redraw the above diagram

Area of triangle `ABC=`Area triangle `ADB-`Area triangle `ADC`

Area of triangle `ABC=1/2timesDBtimesAD-1/2timesDCtimesAD`

You can remove `1/2AD`

Area of triangle `ABC=1/2AD(DB-DC)`

And because `DB-DC=CB`

We can now say:

Area of triangle `ABC=1/2ADtimesCB`

**NOTE:**

Slanting triangles are rare and it’s still best to think of areas of triangles in a rectangle.

# Slanting triangles

Even for triangles shaped as below, the area of a triangle = base x height and half it.

The proof (but you don’t need it) is as follows:

Redraw the above diagram

Area triangle `ACB=`Area triangle `ADB-`Area triangle `ADC`

Area triangle `ABC=1/2timesDBtimesAD-1/2timesDCtimesAD`

You can remove `1/2AD`

Area of triangle `ABC=1/2AD(DB-DC)`

And because `DB-DC=CB`

We can now say:

Area of triangle `ACB=1/2ADtimesCB`

**NOTE:**

Slanting triangles are rare and it’s still best to think of areas of triangles as a rectangle.